Food mapping approaches for understanding food system transformations in rapid-growth city regions in the Global South - Liddy, Heidi; Mowlds, Sinead; McKeown, Peter C.; Lundy, Mark M.; Spillane, Charles (Frontiers Media, 2023)
The world’s food systems are rapidly changing due to socioeconomic, environmental, and demographic changes, globalization, and urbanization. Urban regions connect urban food consumption with rural food production and are associated with rapid dietary transitions in developing counties. Despite urbanization being a key driver of city-regional and global food system transformations, city-regional food systems (particularly in developing countries) are under-researched. Although the importance of dynamic urban and peri-urban food systems has led to new frameworks and approaches for mapping food flows within urban regions, our study highlights both opportunities and limitations to food mapping in high-growth city regions in the Global South. We review existing approaches to food mapping using three contrasting city-regional food systems as case studies, namely, Bahir Dar (Ethiopia), Hanoi (Vietnam), and Cali (Colombia), and identify priorities for future progress. These include temporal dimensions of food access; nutritional outcomes of food flows; economic, cultural, and ethnic factors affecting consumer behavior; and how consumption of healthier foods could be enabled by decision-making throughout food supply chains. In addition, the roles of food loss and waste could also be more specifically considered. We conclude that providing a more comprehensive and nutrition sensitive understanding of city-regional food systems can guide evidence-based interventions and activities to enable transitions to healthier, equitable, and more sustainable urban food systems.